A GENETIC ALGORITHM APPROACH TO THE SELECTION OF CLOUD COMPUTING SERVICES - Samurol @ Mohd Faisal, Narissa Sophea (IRC, 2019)
This paper will discuss on the use of Genetic Algorithm (GA) approach in the selection of cloud services, which is widely used by organizations to enhance their business efficiency. Quality of Service (QoS) is an important factor in the selection of cloud services. This approach is expected to provide the cloud service that satisfies the user’s requirements most according to the QoS requirements provided by the user.